International Migration and Gender Discrimination among Children Left Behind - Antman, Francisca M (American Economic Review, 2011)
This paper considers how international migration of the head of household affects the allocation of resources toward boys relative to girls within households remaining in the home country. I address the endogeneity of migration with a differences-in-differences style regression model that compares those households in which migrants have already returned home with those in which migrants are still away. The evidence suggests that while the head of household is away a greater fraction of resources are spent on girls relative to boys, but upon his return, this pattern is reversed.